2015
DOI: 10.1021/jo5027244
|View full text |Cite
|
Sign up to set email alerts
|

Ring Closure of Azo Compounds to 1,2-Annulated Benzimidazole Derivatives and Further Evidence of Reversibility of the Azo-Coupling Reaction

Abstract: The reaction between 1,3,5-tris(N,N-dialkylamino)benzene derivatives and 2 equiv of p-substituted benzenediazonium salts gives dicationic species which collapse to new benzimidazole derivatives with expulsion of p-substituted anilines. The presence of electron-withdrawing groups on the benzenediazo moiety of the dicationic species plays a key role in this unexpected ring closure reaction. The observed chemical behavior has been rationalized in terms of the already reported reversibility of azo coupling reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…The six-membered cyclic urea moiety is also found in a number of drugs, such as well-known barbiturates, the anti-HIV drug lopinavir, 12 the antibiotic sparsomycin, 13 and the actively studied anticancer agent troxacitabine. 14 Other examples of cyclic ureas of biological importance include 1,3-diazepinone derivatives, which possess anti-HIV [15][16][17][18][19][20][21][22] and anticancer [23][24][25][26] activity and were proposed for the treatment of Alzheimer's and Parkinson's disease. 27 The conventional approach to cyclic ureas involves carbonylation of variously substituted diamines with phosgene.…”
Section: Published As Part Of the Special Topic Recent Advances In Ammentioning
confidence: 99%
“…The six-membered cyclic urea moiety is also found in a number of drugs, such as well-known barbiturates, the anti-HIV drug lopinavir, 12 the antibiotic sparsomycin, 13 and the actively studied anticancer agent troxacitabine. 14 Other examples of cyclic ureas of biological importance include 1,3-diazepinone derivatives, which possess anti-HIV [15][16][17][18][19][20][21][22] and anticancer [23][24][25][26] activity and were proposed for the treatment of Alzheimer's and Parkinson's disease. 27 The conventional approach to cyclic ureas involves carbonylation of variously substituted diamines with phosgene.…”
Section: Published As Part Of the Special Topic Recent Advances In Ammentioning
confidence: 99%
“…Previously, we reported that the reactions of some 1,3,5‐triaminobenzenes with 2 equiv. of 3 in CD 3 CN afford the products of the double attack , . This outcome was also observed when the reaction was performed directly in CD 3 CN at –30 °C in an NMR tube with the reagents in equimolar amounts without the complete dissolution of the triaminobenzene derivative, as shown in Scheme for the reaction between tris( N ‐piperidinyl)benzene ( 8 ) and 3 .…”
Section: Resultsmentioning
confidence: 60%
“…We emphasize that the solubility of 8 played an important role in obtaining the disubstituted derivative instead of the expected monosubstituted compound, because the reaction mixture initially contains a large excess of 3 with respect to 8 , which is present mostly as a solid. Attempts to obtain the trisubstituted products from 8 failed, probably because other processes occur for the disubstituted derivative . Clearly, compound 9 H, which bears two positive charges, is not susceptible to further electrophilic attack to form the trisubstituted derivative in the crude reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
“…The principal method for the synthesis of azoic compounds is the azo-coupling reaction, a kind of electrophilic substitution reaction, that is one of the most important and versatile methodologies in organic synthesis [3,4]. From many years, we are studying aromatic substitution reaction, both electrophilic and nucleophilic, including azo-coupling reaction [5][6][7][8]. Now we report the synthesis, by azo-coupling reaction, of a novel azo compound, namely 3,5-dimethoxy-2-[(4-methoxyphenyl)diazenyl]phenol.…”
Section: Introductionmentioning
confidence: 99%